1485=-11(9x+9)

Simple and best practice solution for 1485=-11(9x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1485=-11(9x+9) equation:


Simplifying
1485 = -11(9x + 9)

Reorder the terms:
1485 = -11(9 + 9x)
1485 = (9 * -11 + 9x * -11)
1485 = (-99 + -99x)

Solving
1485 = -99 + -99x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '99x' to each side of the equation.
1485 + 99x = -99 + -99x + 99x

Combine like terms: -99x + 99x = 0
1485 + 99x = -99 + 0
1485 + 99x = -99

Add '-1485' to each side of the equation.
1485 + -1485 + 99x = -99 + -1485

Combine like terms: 1485 + -1485 = 0
0 + 99x = -99 + -1485
99x = -99 + -1485

Combine like terms: -99 + -1485 = -1584
99x = -1584

Divide each side by '99'.
x = -16

Simplifying
x = -16

See similar equations:

| 14x-8x=42 | | -15=.5[x+6] | | 5(5p+4)+4(3p+2)= | | 2n+25=4n+23 | | 190/50 | | 7w+2w=45 | | y-10=-x+2 | | x-3.6=1.4 | | 5k-4=2k+11 | | -5+8k=7k+4-7 | | Ab/c=xy/z | | 3x(2xy)(-3x^5y^2)= | | 15/6xt=81 | | X=5x-2x+3x-4x+5x | | 6^1*0+2%2 | | v-2=10-v | | 1.13=p-1.3 | | -4-4n=1-5n | | x+6*x-9=30 | | 3[x-2]=27 | | 2y=2y+44 | | 40+4x=12(x+20) | | 5-8m=14-5m | | 1.7-x=1.2 | | g/-4=-4.21 | | x+6x*-9=30 | | 5x^4-40x^2=0 | | M+23=94 | | 5k+4=3k-2k | | 3.1=x-1.5 | | 4/6r=5 | | x+6a*-9=30 |

Equations solver categories